Power Generation from Coal-A review - Sarker, Mridul; Chowdhury, Debasish; Hossain, Iqbal (Journal of Chemical Engineering, 2014)
Power generation from coal is an essential need to meet world?s energy demand. There are two major challenges in coal-based power generation: improving the efficiency and reducing the emissions level. In fact, these challenges have been under research for a long time. This article focuses on the recent developments of process technologies and coal treatment to improve the performance of coal?based power plant. Barriers to the adoptions of modern developments and additional needs in research are also addressed. DOI: http://dx.doi.org/10.3329/jce.v27i2.17802 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 50-54